A one-year prospective study of infectious etiology in patients hospitalized with acute exacerbations of COPD and concomitant pneumonia - Ko, Fanny W.S. (Respir Med, 2008)
AIM: This study assessed the infectious etiology of patients hospitalized for acute exacerbations of chronic obstructive pulmonary disease (AECOPD) with concomitant pneumonia. METHODS: Patients admitted to medical wards in an acute hospital were recruited prospectively from May 1, 2004 to April 30, 2005. Sputum culture, blood culture, paired serology, and nasopharyngeal aspirates (NPA) viral culture and polymerase chain reaction (PCR) studies were performed. Spirometry was assessed in stable phase at 2–3 months post-hospital discharge. RESULTS: Seventy eight subjects were admitted for AECOPD with concomitant pneumonia. The mean (SD) age was 77.1 (7.5) years, with FEV(1) of 41.5 (20.8)% predicted normal. Overall, an infectious etiology could be established in 48.7% of the subjects. Among the 71 subjects with sputum collected, 40.8% had positive bacterial culture. The commonest bacteria identified were Streptococcus pneumoniae (8[11.3%]), Pseudomonas aeruginosa (7[9.9%]) and Haemophilus influenzae (7[9.9%]). Among the 66 subjects with NPA collected, 9.0 and 12.2% had positive viral culture and PCR results, respectively. The commonest viruses identified by NPA PCR were influenza A (4[6.1%] subjects) and rhinovirus (2[3.0%]). Paired serology was positive in 4.4%. Patients on high dose inhaled corticosteroid (ICS) (>1000 mcg beclomethasone-equivalent/day) had a higher rate of positive sputum bacterial culture than those on low-medium dose of ICS (50.0% vs 18.2%, p = 0.02). CONCLUSION: An infectious etiology could be established in about half of patients hospitalized with AECOPD and concomitant pneumonia. The majority of identifiable causes were bacterial. Patients on high dose ICS might have impaired airway defense as reflected by the higher rate of positive sputum culture.